GROWTH AND RESULTS OF CORN AND NUTS IN THE INTERCROPPING SYSTEM - Sari, Lili Agustina (Jurnal Pertanian, 2019)
The purpose of this study was to determine the growth and yield of corn and cowpea after planting in the intercropping system. Conducting research at the Kalitirto Agricultural Research and Development (KP4) Educational Garden, Berbah, Yogyakarta friend. A Complete Randomized Block Design with 3 replications was used in the study. Experimental intercropping of corn and cowpea based on additive series system. The first factor is the population of cowpea is without cowpea, 1 row, 2 rows, and 3 rows of cowpea. The second factor is the spacing is 100 cm x 20 cm and 80 cm x 25 cm. Research on cowpea monoculture as a comparison.The results obtained (1) insertion of cowpea, and spacing of corn did not affect the yield of corn per hectare, but affect the yield of cowpea. (2) The combination of 100 cm x 20 cm corn spacing treatment with the insertion of 2 rows of cowpea gives the highest Land Equity Ratio value of 1.42.